Attitude to counseling and testing for HIV and knowledge about prevention of mother to child transmission of HIV in men accompanying antenatal attendees at a tertiary care hospital in South India - Krishnamoorthy, Nivedita; Navis, Fatima Shanthini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Parent to child transmission is the second most common route of transmission of HIV in India contributing to 5% of new infections. This is due to underutilization of the components of PPTCT among pregnant women . As male partners remain the main decision makers in the family and influence their wife’s behaviour, poor awareness and negative attitude of men towards testing and treatment of HIV is a hindering factor in the successful implementation of the program. Therefore this study was carried out to study the awareness of men regarding HIV and PPTCT and also to assess their attitude towards testing and treatment in an antenatal clinic setting. Methods: This is a cross sectional descriptive institution based study conducted in Sri Manakula Vinayagar Medical College and Hospital, Puducherry, India. The study participants were men who accompanied their pregnant wife to the antenatal clinic. A pretested, predesigned questionnaire was used as the survey tool to assess the knowledge of these men about PPTCT services and also to assess their attitude towards HIV testing during pregnancy. The collected data was entered in SPSS and analyzed using descriptive statistics. Results: Among participants only 68% were aware that a HIV positive mother could transmit infection to her baby and more than half of the participants were not aware that breast feeding could cause vertical transmission. Nearly 39% of the participants were not aware that mother to child transmission can be curtailed by giving ART during pregnancy. Acceptance for HIV testing was fairly good even before pretest counseling to the extent of 88.6% of the participants. Among the participants who did not want to get tested for HIV, 52.9% assumed that their HIV status will be the same as that of their wife whereas 29.4% said that they were not comfortable undergoing the test along with their wife. Conclusions: The present study shows that men lacked awareness about the concept of vertical transmission of HIV and also the various aspects of prevention of maternal to child transmission of the infection. Their attitude towards testing was positive even though they were not aware of its implications. Media should be used to create awareness and couple counseling and testing should be promoted in all PPTCT centers thereby increasing the male participation in the PPTCT program.